Advances in biogas valorization and utilization systems: A comprehensive review. (10th November 2020) - Kapoor, Rimika; Ghosh, Pooja; Tyagi, Bhawna; Vijay, Virendra Kumar; Vijay, Vandit; Thakur, Indu Shekhar; Kamyab, Hesam; Nguyen, Dinh Duc; Kumar, Ashok
Abstract: The emission of greenhouse gases and global warming are the major environmental concerns that has affected the normal geochemical cycles and climate conditions on the earth. However, a controlled production, conversion and utilization of these gases for energy generation in day to day activities of human beings can solve the problem of climate change effectively. Biogas has been recognized as a source of renewable energy available to considerably accelerate the socio-economic development. It is a multifaceted fuel containing methane, carbon dioxide and water vapors with multiple utilization options. Biogas can be valorized either directly or indirectly for various applications like the production of value-added chemicals or as a replacement of natural gas. This review article provides an in-depth analysis of various biogas valorization methods (physical, chemical and biological) for its efficient and eco-friendly utilization. The review intends to fill-up the knowledge gap through critically reviewing biogas cleaning and upgrading methods for biomethane and bio-CO2 production for various applications including power plants, transport and value-added chemicals. The review article also highlights the conversion of biogas into fine chemicals and products of commercial importance. Chemical, biological and hybrid systems of biogas utilization are described in detail. The opportunities and impediments associated with the valorization of biogas, biomethane and bio-CO2 have also been discussed. The paper highlights that most of the approaches to the implementation of biogas are in their infancy stage. It also identifies the bottlenecks, policies and future research and developments that are still needed in this relatively emerging field. Graphical abstract: Image 1 Highlights: Biogas is a multifaceted fuel with multiple utilization options. Direct and indirect biogas valorization avenues. Critical review of biogas cleaning and upgrading methods. Conversion of biogas into value added products. Role of microbes in biogas valorization.